2001
DOI: 10.1080/10357710120055094
|View full text |Cite
|
Sign up to set email alerts
|

Public consultation or political choreography? The Howard Government's quest for community views on defence policy

Abstract: Howard Government released a public information paper on defence which set in train a process of public consultation in which the people's views were sought on a range of defence and defence-related issues. This paper examines why the Government chose to go to the people, how and by whom the community consultation was conducted, who was consulted and listened to, and how what was heard at the public meetings component of the process was both interpreted and reported. The paper concludes that the public consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Their results support other case-study analyses' findings of (economic) elite influence on public policy-making (J. Carr 2012; Kaehne and Taylor 2016;Parkins and Sinclair 2014). Studies also highlight government officials' role in limiting consultation's policy impact (Carvalho, Pinto-Coelho, and Seixas 2016;Cheeseman and Smith 2001). Here, we respond to the paucity of systematic analyses of consultation's policy outcomes by quantitatively analyzing the relationship between public submissions and resultant legislation across different submitter groups.…”
Section: Outcome-based Evaluationssupporting
confidence: 78%
See 1 more Smart Citation
“…Their results support other case-study analyses' findings of (economic) elite influence on public policy-making (J. Carr 2012; Kaehne and Taylor 2016;Parkins and Sinclair 2014). Studies also highlight government officials' role in limiting consultation's policy impact (Carvalho, Pinto-Coelho, and Seixas 2016;Cheeseman and Smith 2001). Here, we respond to the paucity of systematic analyses of consultation's policy outcomes by quantitatively analyzing the relationship between public submissions and resultant legislation across different submitter groups.…”
Section: Outcome-based Evaluationssupporting
confidence: 78%
“…Morinville and Harris 2014), the politics of process design (e.g. Cheeseman and Smith 2001), and how process design and implementation affects participation (e.g. Halseth and Booth 2003).…”
Section: Process-based Evaluationsmentioning
confidence: 99%
“…Quittkat (2011) shows that in European consultations, the European Commission tends to favour business and industry organizations over those representing the interests of the environment, trade unions and consumers (Quittkat, 2011). Cheeseman and Smith (2001) come to a similar conclusion in a study of a large-scale public consultation on Australian defence policy. The importance of organizational resources corresponds to studies on interest group access, showing that organizations with plenty of members or professional resources have better access to policymaking institutions (Bouwen, 2002;Hansen, 1994;Maloney et al, 1994;Uhrwing, 2001).…”
Section: Introductionmentioning
confidence: 50%
“…Cheeseman and Smith [36] found that a consultative policy-development process resulted in little actual influence on policy direction, but that the consultation process garnered support for policies already in train. If anything, the RET review process allowed the Australian Government to cite support from a variety of stakeholders, including industry and the general public, with regard to the implementation of policies to support renewable energy in Australia.…”
Section: Climate Change Authority Review Recommendations and Governmementioning
confidence: 98%